2020
DOI: 10.1093/jac/dkaa200
|View full text |Cite
|
Sign up to set email alerts
|

A novel colistin adjuvant identified by virtual screening for ArnT inhibitors

Abstract: Background Colistin is a last-resort treatment option for many MDR Gram-negative bacteria. The covalent addition of l-aminoarabinose to the lipid A moiety of LPS is the main colistin resistance mechanism in the human pathogen Pseudomonas aeruginosa. Objectives Identification (by in silico screening of a chemical library) of potential inhibitors of ArnT, which catalyses the last committed step of lipid A aminoarabinosylation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…To assess the colistin adjuvant activity of the newly synthesized compounds ( 2–15 ), we first performed the same screening assay that allowed the identification of compound 1 as a colistin potentiator. 22 Briefly, a reference P. aeruginosa strain evolved in vitro toward colistin resistance (PA14 col R 5), characterized by a colistin MIC of 64 μg/mL and that was demonstrated to depend on lipid A aminoarabinosylation for colistin resistance, 45 , 46 was cultured in the presence of a fixed, subinhibitory concentration of colistin (8 μg/mL) and different concentrations of each compound of interest (4–64 μM). As control, the effect of the compounds on PA14 col R 5 growth in the absence of colistin was also assessed.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the colistin adjuvant activity of the newly synthesized compounds ( 2–15 ), we first performed the same screening assay that allowed the identification of compound 1 as a colistin potentiator. 22 Briefly, a reference P. aeruginosa strain evolved in vitro toward colistin resistance (PA14 col R 5), characterized by a colistin MIC of 64 μg/mL and that was demonstrated to depend on lipid A aminoarabinosylation for colistin resistance, 45 , 46 was cultured in the presence of a fixed, subinhibitory concentration of colistin (8 μg/mL) and different concentrations of each compound of interest (4–64 μM). As control, the effect of the compounds on PA14 col R 5 growth in the absence of colistin was also assessed.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Recently, a unique in-house library of natural products available in our group was screened in silico against the catalytic site of the ArnT enzyme to identify putative inhibitors of the Ara4N-dependent colistin resistance mechanism. 22 This led to the selection of the ent -beyerene diterpene 1 (formerly known as BBN149), isolated from the leaves of Fabiana densa var. ramulosa , with a colistin adjuvant activity versus colistin-resistant P. aeruginosa strains, without any significant effect on colistin-susceptible strains.…”
Section: Introductionmentioning
confidence: 99%
“…Colistin is considered as an antibiotic of last resort for treating severe CRKP infections, because of increasing microbial resistance and associated toxicity ( Elnahriry et al., 2016 ; Schwarz and Johnson, 2016 ; Rojas et al., 2017 ; Wang et al., 2018 ; Ghirga et al., 2020 ). In this study, we found a 10.5% of CRKP resistant to colistin.…”
Section: Discussionmentioning
confidence: 99%
“…A novel colistin adjuvant that inhibits ArnT, which catalyzes the last committed step of lipid A aminoarabinosylation and is associated with a positive charge increase in cells [ 7 ], was identified using in silico screening [ 11 ]. Therefore, the strategy appears to be a promising candidate for lead optimization in the development of colistin resistance inhibitors.…”
Section: Introductionmentioning
confidence: 99%